Dehydration of xylose to durfural and Its valorization via different multicomponent reactions using sulfonated silica with magnetic properties as recyclable catalyst - Martínez, José J. (2014)
Sulfonated silica with magnetic properties was studied for dehydration of xylose to furfural and posteriorly for furfural valorization through the Biginelli and Hantzsch multicomponent reactions. Eleven polysubstituted heterocycles were obtained in excellent yields and without any side-product (81-91 %), using a multicomponent green methodology. The presence of Fe3O4 particles allows an easy separation from the reaction medium giving a high yield in the reusability studies.